Old-Age Provision and Homeownership - Fiscal Incentives and Other Public Policy Options (Springer International Publishing, 2018)
In light of demographic change and the growing problems of traditional old-age security systems, this book discusses two essential instruments in connection with privately providing for old-age security: (1) savings in private pension schemes and (2) building up equity for home-ownership. Further, it assesses the relationship between the two instruments and offers a unique overview of the latest market developments. In order to represent the profound differences between the individual member states of the EU, this book features six country-specific studies - covering Germany, Hungary, Ireland, Italy, the Netherlands and the United Kingdom - that provide detailed insights into the complexity of local private pension schemes, mortgage markets, and housing markets. Lastly, the book discusses public policies and fiscal incentives intended to better integrate residential property with private pensions. It will appeal to both, private households seeking to build up old-age security, as well as policy makers interested in providing secure pension schemes. .